Liposomal encapsulated alpha-lipoic acid, benfotiamine and curcumin prevent overfeeding mediated increases in waist circumference - Grimm, Nathan Carlisle, author; Bell, Christopher, advisor; Dooley, Gregory, committee member; Hickey, Matthew, committee member (Colorado State University. Libraries, 2017)
INTRODUCTION: To determine if liposomal (L) encapsulated alpha-lipoic acid (0.5g), benfotiamine (0.5g) and curcumin (2.0g) (ABC) would prevent the unfavorable metabolic consequences of sedentary high-fat overfeeding in healthy young adults. METHODS: 29 young (18-30 years), healthy, physically active men and women were randomly assigned to ingest placebo (n=9), ABC (n=10), or L-ABC (n=10) twice daily for 28 days. Between days 22 and 28 all participants abstained from their normal regular exercise and consumed a high calorie, high fat diet. RESULTS: On Day 29, circulating alpha lipoic acid was greater (p<0.01) in L-ABC (412±73 ng/mL) compared with ABC (154±33 ng/mL). During the sedentary high fat overfeeding, dietary intake was not different (p>0.60) between groups (~3,400 kcal/day; ~50% from fat). Sedentary high fat overfeeding increased (p<0.05) waist circumference in the placebo (+2.7±2.7 cm) and ABC (+3.3±2.0) groups but not the L-ABC group (+0.7±2.7). The magnitudes of increase (p<0.05) in body mass (1.7±0.3 kg), fat mass (0.7±0.2 kg), and blood pressure (3±1 mmHg) and decrease (p<0.05) in insulin sensitivity (Matsuda Index: -2.9±0.9) after overfeeding were not different between groups (all p>0.50). DISCUSSION: Liposomal encapsulated alpha-lipoic acid, benfotiamine and curcumin: 1) promoted alpha-lipoic acid bioavailability; and, 2) prevented sedentary high-fat overfeeding mediated increases in waist circumference in usually active healthy young adults. These data may have important public health implications for periods of inactive overconsumption such as during seasonal celebrations.